Frontier and hotspot evolution in cerebrotendinous xanthomatosis: a bibliometric analysis from 1993 to 2023 - Luo, Fei; Ding, Yali; Zhang, Shanyun; Diao, Juanjuan; Yuan, Bin (Frontiers in Neurology, 2024)
Background Cerebrotendinous xanthomatosis (CTX) is an autosomal recessive disease associated with lipid metabolic disorders. Because of its clinical diversity and rarity, the diagnosis is often unclear. However, there is still a lack of reports on bibliometric analysis of CTX. The aim of this study was to assess the progress and research developments of CTX over the past three decades, identify emerging trends, and establish novel directions for future research. Methods The eligible literature were screened from the Web of Science Core Collection (WoSCC) database. The annual publication, countries, institutions, authors, journals, keywords and references were visually analyzed by Microsoft Excel 2019, CiteSpace 6.2.R4, VOSviewer 1.6.18 and online bibliometrics website (https://bibliometric.com/). Results A total of 561 publications from WoSCC were included in this study. The United States is the country with the largest number of publications, and Karolinska Institutet is the institution with the largest number of publications. Björkhem I. ranks as the most published and cited author in the last three decades. Journal of Lipid Research is the most widely published and cited journal. The strongest burst of keywords is “diagnosis.” Conclusion Unraveling the pathogenesis of CTX and improving its diagnosis and treatment continue to be critical challenges that require urgent attention. Future research endeavors will be centered on enhancing the efficiency and accuracy of early diagnosis and intervention.